The Role of Guidance and Counseling Teachers in Improving Students' Morals According to the Perspective of the Book of Nashoihul 'Ibad by Imam An-Nawawi - Ainayya Husna; Ahmad Darlis; Taufik Hidayat Daulay; Fery Fadli; Nurul Fadhilah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Moral decline is an increasingly deep and complex issue in today's society. This article investigates the various factors that contribute to the decline in moral values. One of the main factors is the increasingly rampant influence of technology and mass media, which often promote a destructive consumer and hedonistic culture. In the context of Islamic education, the role of a guidance and counseling teacher has a very important dimension in shaping students' morals. Morals as an integral part of Islamic teachings are the moral and ethical foundations that must be formed and strengthened in education. This is in accordance with Article 3 of Law Number 20 of 2003 concerning the National Education System, therefore good character for the nation's successors is very necessary. There has been much discussion about how character emerges or appears in a person. This study uses a qualitative approach that uses literature studies (library search). This article will discuss how to improve morals from the perspective of the Book of Nashoihul 'Ibad by Imam An-Nawawi, what is real morals and what is the role of guidance and counseling teachers in this regard.